Very High Energy Solar Energetic Particle Events and Ground Level Enhancement Events: Forecasting and Alerts - N. Crosby; H. Mavromichalaki; O. Malandraki; M. Gerontidou; M. Karavolos; D. Lingri; P. Makrantoni; M. Papailiou; P. Paschalis; A. Tezari (Space Weather)
Abstract A Ground Level Enhancement (GLE) event can be observed as an increase in the background of ground‐based neutron monitor observations and is often associated with an increase of >500 MeV space‐based proton flux measurements. GLE events begin as very high‐energy SEP events associated with GeV protons. For such events to be detected at sea level, proton energies must exceed about 433 MeV. Since the increased flux of such particles can be a major problem to technology in space and on Earth and pose a threat for human health, developing real time warning systems is of great importance. GLE Alert++ is a product, built by the Athens Cosmic Ray Group of the National and Kapodistrian University of Athens, that issues alerts when a GLE event starts to register and is based on ground‐based neutron monitor observations. From the space‐based approach, the HESPERIA UMASEP‐500 product, jointly developed within the framework of the EU HORIZON2020 HESPERIA project by the Universidad de Malaga, Spain and National Observatory of Athens, Greece, provides forecasts of GLE events and >500 MeV protons relying on GOES satellite Soft X‐Ray and high energy proton observations. These two products are fully integrated as federated products on the ESA SWE Portal and are provided as part of the ESA Space Safety Program Space Weather Service Network. In this paper we present how the products were built, provide examples of their outputs as seen on the ESA SWE Portal, and show how the products complement each other and how using them together can in some instances provide more information for users of these services.